Concurrent collaboration in research and development - Ale Ebrahim, N.; Ahmed, S.; Taha , Z. (2008)
Integration is the essence of current research and development (R&D) activity in many organizations. Integration can be established in various ways depending on the type, size and intricacy in organizational functions and products. Nevertheless, research and development (R&D) has become an inevitable function in most manufacturing companies in order to develop their own product niches for their survival in the prevailing highly completive market environment. Research and development functions are fundamental drivers of value creation in technologybased enterprises. Of creating and maintaining a vibrant R&D environment, organizations individually or collectively need to incorporate virtual R&D team. A virtual R&D team can introduce new product in less lead time than by conventional R&D working. Therefore, how to increase the possibility of having more successful R&D is a critical issue for enterprises. This paper examines the current approach of collaboration in R&D issues from the perspective of their impact on virtual R&D team in enterprises and compares the findings with the other concepts of concurrent collaboration. By reviewing literature and theories, the paper firstly presents the definition and characteristics of virtual R&D teams. A comparison of different types of virtual R&D teams along with the strengths and limitations of the preceding studies in this area are also presented. It is observed that most of the research activities encourage and support virtual R&D teams applicable to enterprises. Distinctive benefits of establishing virtual R&D team have been enumerated and demand future attention has been indicated in the paper.